Change in fasting plasma glucose and incident type 2 diabetes mellitus: results from a prospective cohort study. Issue 5 (23rd May 2016) - Mozaffary, Amirhossein; Asgari, Samaneh; Tohidi, Maryam; Kazempour-Ardebili, Sara; Azizi, Fereidoun; Hadaegh, Farzad
Abstract : Objective: To investigate the association between changes in fasting plasma glucose (FPG) values and incident type 2 diabetes (T2D) in a cohort of the Iranian population. Design: Prospective cohort study. Setting: This study was conducted within the framework of the Tehran Lipid and Glucose Study (TLGS) to investigate the association between change in FPG between baseline examination (1999–2001) and the second visit (2002–2005) with incident T2D. Participants: A total of 3981 non-diabetic participants aged ≥20 years. Outcome measure: T2D was defined if the participant was using antidiabetic drugs or if FPG was ≥7 mmol/L or if the 2 h post-challenge plasma glucose (2-hPCG) was ≥11.1 mmol/L. Results: During a median follow-up of 6.17 years, after the second examination, 288 new cases of T2D were identified. In a multivariate Cox proportional hazard analysis using age as timescale, we presented a simple model including FPG change (HR 1.19, 95% CI 1.07 to 1.33) and baseline waist circumference (WC) (HR 1.004, 95% CI 1.001 to 1.008) with a discriminative power (C-index) of 72%. Furthermore, we showed that the highest quartile of FPG change enhanced the T2D risk to 1.65 (95% CI 1.2 to 2.27) compared with the lowest quartile (p for trend=0.004).The independent risk of FPG change resisted further adjustment with 2-hPCG change. Adding the 2-hPCG change only slightly increased the discriminative power of the model including FPG change and baseline value of WC (0.73% vs 0.72%). After the study population had been limited to those with normal fasting glucose/normal glucose tolerance, FPG change remained an independent predictor (HR 1.57, 95% CI 1.31 to 1.88). Conclusions: Two measurements of FPG obtained about 3 years apart can help to identify populations at risk of incident T2D independently of important traditional risk factors and their changes, including 2-hPCG change.